Application and optimization of bioengineering strategies in facilitating tendon–bone healing - Chenhui Yang; Changshun Chen; Rongjin Chen; Fei Yang; Hefang Xiao; Bin Geng; Yayi Xia (BioMedical Engineering OnLine)
Abstract Tendon–bone insertion trauma is prevalent in both rotator cuff and anterior cruciate ligament injuries, which are frequently encountered conditions in the field of sports medicine. The main treatment for such injuries is reconstructive surgery. The primary determinant impacting this process is the graft's capacity to integrate with the bone tunnel. In recent years, researchers have attempted to use a variety of methods to facilitate tendon–bone healing after reconstructive surgery. Such as the implantation of biological materials, cytokines and the local application of permanently differentiated cells from various sources. However, there are limitations to the efficacy of one therapy alone in facilitating tendon–bone healing. Therefore, researchers are trying to combine strategies to overcome this conundrum. At present, most studies are based on biomaterial combined with other therapeutic strategies for tissue repair and regeneration. Biomaterials mainly include the application of bioengineering scaffolds, hydrogels and bioabsorbable interference screws. By conducting a thorough review of relevant literature, this study provides a comprehensive overview of the present research progress in enhancing tendon–bone healing using biomaterials. Additionally, it explores the potential benefits of combining biomaterials with other approaches to promote tendon–bone healing. The ultimate goal is to offer insights for future basic research endeavors and establish a solid groundwork for advancing clinical applications in the near future.